2021
DOI: 10.3389/fpls.2021.679059
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Quantitative Trait Loci Controlling the Content of Phenolic Compounds in an Asian Plum (Prunus salicina L.) F1 Population

Abstract: Consumption of fresh fruit is known to protect against non-communicable diseases due to the fruit's content in compounds with an antioxidant capacity, among them is polyphenols. Asian plums (Prunus salicina L.) accumulate more than 40 phenolic compounds, with a remarkable diversity in their profiles, depending on the variety and environmental conditions. Although candidate genes have been indicated to control this trait, the loci controlling its phenotypic variation have not yet been defined in this species. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…Both the F1 progeny and the parents showed greater contents of flavan-3-ols in the skin than in the flesh in T1 and T2. Flavan-3-ol contents agree with the total amount of phenolic compounds of the Japanese plum fruits, which have higher accumulation in the skin than in the flesh (Cabrera-Bañegil et al, 2020;Valderrama-Soto et al, 2021). Also, we observed a greater accumulation of C and EC in T2 than T1.…”
Section: Flavan-3-ol Content Of Japanese Plum Fruitssupporting
confidence: 86%
See 4 more Smart Citations
“…Both the F1 progeny and the parents showed greater contents of flavan-3-ols in the skin than in the flesh in T1 and T2. Flavan-3-ol contents agree with the total amount of phenolic compounds of the Japanese plum fruits, which have higher accumulation in the skin than in the flesh (Cabrera-Bañegil et al, 2020;Valderrama-Soto et al, 2021). Also, we observed a greater accumulation of C and EC in T2 than T1.…”
Section: Flavan-3-ol Content Of Japanese Plum Fruitssupporting
confidence: 86%
“…As T2 samples were used as a comparison to verify the observed trends in T1, we decided not to sample these 15 seedlings. Samples employed in this study were the same as those from the studies reported by Salazar et al (2017Salazar et al ( , 2020 and Valderrama-Soto et al (2021). Fruits were harvested following the criteria reported by Contador et al (2016), with chlorophyll absorbance index (IAD) values between 1 and 1.40 units and a firmness close to 40 N. After harvest, the fruits were frozen using liquid nitrogen and stored at -20 • C until sample preparation.…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations